HORACE's SERMONES BOOK 1 CREDENTIALS FOR MAECENAS - Weeda, Leendert (De Gruyter, 2019)
This monograph interprets Sermones book 1 as a collection of Horace's credentials for Maecenas and traces his efforts in getting accepted as an associate of the latter after his miscalculation in joining Brutus. Although Horace regularly reflects on his poetic orientation and standards of good poetry, his primary objective was his self-presentation. The volume also examines his commentary on contemporary socio-political themes.